2000
DOI: 10.1021/ie990740k
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Separation with a Copper(II)-Loaded Polymeric Ligand Exchanger

Abstract: The present study characterizes a new polymeric ligand exchanger (PLE) for enhanced separation of trace anionic ligands, and investigates related interfacial chemistry. Compared to conventional anion exchangers, the PLE exhibited significantly different selectivity sequence and elution profiles, which may be utilized in enhancing selective capture of target solutes and/or chromatographic separation of anionic ligands. Experimental data indicate that the exchanger phase pH is significantly higher across the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 12 publications
(40 reference statements)
0
39
1
Order By: Relevance
“…From a thermodynamic viewpoint, the contribution of DG 0 EL in eqn [21] may be viewed as comparable for both IRA-958 and DOW 3N-Cu. However, the DG 0 SP term is practically zero for IRA-958, but highly negative for DOW 3N-Cu (Zhao and SenGupta, 2000).…”
Section: Electrostatic Interactionmentioning
confidence: 96%
See 3 more Smart Citations
“…From a thermodynamic viewpoint, the contribution of DG 0 EL in eqn [21] may be viewed as comparable for both IRA-958 and DOW 3N-Cu. However, the DG 0 SP term is practically zero for IRA-958, but highly negative for DOW 3N-Cu (Zhao and SenGupta, 2000).…”
Section: Electrostatic Interactionmentioning
confidence: 96%
“…For PLEs, intraparticle diffusion is more likely the rate-limiting step (Zhao, 1997;Zhao andSenGupta, 1998, 2000;An et al, 2005). In a prior study on phosphate sorption, Zhao and SenGupta (2000) identified that intraparticle diffusion is the rate-limiting step during sorption of phosphate to DOW 3N-Cu.…”
Section: Electrostatic Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to this challenge and the increasingly stringent environmental regulations, many new treatment methods have been investigated (Fu et al 2007;Korshin et al 2007;Zhao and SenGupta 2000;Ureña-Nuñez et al 2007). Among these methods, replacement-precipitation process is the most economic and effective way.…”
Section: Introductionmentioning
confidence: 99%